(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: COVID-19 is a viral infection caused by the acute respiratory syndrome virus (SARS-CoV-2), which clinically affects several human body organs. The present study aims to investigate the clinical symptoms of the oral cavity and its severity in patients with COVID-19 referred to Imam Reza Hospital in Tabriz in 1401. Materials and methods: In this descriptive cross-sectional study, 89 patients with COVID-19 positive PCR tests and 89 healthy individuals who met the conditions for inclusion were examined. Patient demographic information, including age, gender, history of underlying diseases, and use of toothbrushes, was recorded. Then the patients were examined by a dentist, and various oral lesions were recorded. Saliva flow rate, lesion intensity, and gingival inflammation rate (based on BOP) were recorded. The results were analyzed by SPSS24 statistical analysis software and the Marie Chi-square test. Results: Oral lesions, including painful and non-painful ulcers in the mucosa, small blisters in the oral mucosa, the presence of petechiae, and the amount of taste disorder in patients with COVID-19 were significantly higher than in healthy individuals. The severity of gingivitis in patients with COVID-19 was significantly higher than in healthy people. The difference in the frequency of oral lesions was observed in both the sick and healthy groups in both men and women and different age groups. Conclusion: COVID-19 can cause aggravation of oral lesions.